Analysis of retrospective natural history data collected from patients with SYNGAP1-related disorders: a preliminary examination of the Citizen database - Matthew R. Scott; Albert Misko; Yang Liu; Oleksandr Sverdlov (Orphanet Journal of Rare Diseases)
Abstract Background SYNGAP1-related disorder (SRD) is a rare neurodevelopmental disorder caused by genetic variants. A major challenge is the characterization of SRD, which requires assessment of several outcomes. We considered natural history data from the Citizen database on 65 patients with SRD in eight data domains: demographics, genetics, growth parameters, standardized clinical scales, developmental skills, neurological examinations, hospitalizations, and seizures. Exploratory analysis tools such as visualizations, summary statistics, and non-parametric statistical modeling were utilized. Results Age at SRD diagnosis (median [IQR] = 3 [2, 5] years; [min, max] = [1, 17] years) was similar by sex. No evidence of a high frequency allele change in SYNGAP1 was found, indicating no dominant variant in this patient population. Growth parameters of SRD children appeared normal in terms of height, weight, and head circumference. Developmental data were indicative of delayed development and language reversion. Standardized assessment data were largely sparse. Neurological exam data demonstrated ataxia and muscle tone issues. Hospitalization data highlighted substantial healthcare burden, largely due to seizures; absence, atonic, and myoclonic seizures were the most common types. Conclusion Citizen data provide important insights into the natural course of SRD. Our findings not only provide utility in clinical practice of SRD but also contribute valuable insights to guide the development of SRD clinical trials. Limitations to our analysis include sparsity of standardized clinical scales data, crude statistical methodology, and bias induced by patients with older ages of diagnoses.